2020
DOI: 10.1186/s12957-020-01891-y
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of organic anion-transporting polypeptide 1B3 predicts a poor prognosis in hepatocellular carcinoma

Abstract: Objective: To detect the expression level of organic anion-transporting polypeptide 1B3 (OATP1B3) in hepatocellular carcinoma (HCC) and to determine the relationship between OATP1B3 expression, clinicopathological features, and prognosis. Methods: Immunohistochemical (IHC) staining was performed to detect the expression of OATP1B3 in 131 HCC specimens and in 89 adjacent nontumorous tissues. Moreover, the expression levels of OATP1B3 in 30 pairs of tumor and matched adjacent nontumorous tissues were detected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…HCC comprises 75-85% of liver cancers and has a poor prognosis [1]. Some studies have shown multiple genes present good predictive potential in assessing HCC prognosis [15][16][17][18]. Recently, the importance of ICI therapy in HCC patients has been proven.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCC comprises 75-85% of liver cancers and has a poor prognosis [1]. Some studies have shown multiple genes present good predictive potential in assessing HCC prognosis [15][16][17][18]. Recently, the importance of ICI therapy in HCC patients has been proven.…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, a model with more genes and gene pairs will attain a higher AUC of OS. Second, our model did not include some earlier reported HCC prognosis genes [15][16][17][18]. Our prediction model only included 3 immune-related gene pairs with 6 genes to assess both the prognosis and treatment sensitivity to immune and targeted therapy of HCC patients, and it was hard to include all genes reported.…”
Section: Table 2 the Chi-square Test Of The Relation Between Risk Sco...mentioning
confidence: 99%
“…HCC accounts for 75–85% of liver cancers and is also the third leading cause of cancer-related death globally, which has a poor prognosis [ 1 ]. Studies have shown that multiple genes play an important role in HCC progression [ 30 34 ]. Currently, immunotherapy has already become a viable option for advanced patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chen et al showed that the OATP1B3 expression was signi cantly reduced in neoplastic tissues compared to that in adjacent non-neoplastic tissues. Moreover, the OATP1B3 lower expression was signi cantly correlated with the tumor size, relapse, tumor differentiation, and tumor node metastasis (TNM) rate in hepatocellular carcinoma 39 .…”
Section: Discussionmentioning
confidence: 99%